Notice of Retraction: Comparative evaluation of SiC/GaN “MOSFET” transistors under different switching conditions - Ghanim Thiab Hasan; Ali Hlal Mutlaq; Kamil Jadu Ali (Bulletin of Electrical Engineering and Informatics, 2022)
Notice of Retraction-----------------------------------------------------------------------After careful and considered review of the content of this paper by a duly constituted expert committee, this paper has been found to be in violation of IAES's Publication Principles.We hereby retract the content of this paper. Reasonable effort should be made to remove all past references to this paper.The presenting author of this paper has the option to appeal this decision by contacting beei@iaescore.com.-----------------------------------------------------------------------The aim of this paper is to conduct a mutual comparison of switching energy losses in cascade gallium nitride (GaN) and silicon "super junction" MOSFET” transistor, in both cases designed for a maximum operating voltage of (650 V). For the analysis of switching characteristics of transistors used double pulse test method by using detailed SPICE simulation model. Data on transient on and off processes were generated using the “LTspice” simulation package in a wide range of drain currents with two different gate resistance values of the tested transistors. The total energy losses in the GaN have been simulated during one transistor at (on and off cycle). The obtained results indicate that the superior switching characteristics of GaN devices for a drain current of (30 A) is five to eight times less than the switching characteristics of silicon “MOSFET” transistor when compared to silicon components, especially during operation of transistors with high drain currents.